IMPLEMENTASI KEBIJAKAN REKRUTMEN DI LINGKUNGAN BADAN PEMBINAAN HUKUM TENTARA NASIONAL INDONESIA - Wihandoyo; Reza Fathurrahman (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2024)
Recruitment within the Indonesian National Army Legal Development Agency (Babinkum TNI) is carried out by the TNI Personnel Staff (Spers TNI). In its implementation, there are many obstacles to meeting the needs of TNI and PNS personnel within the Babinkum TNI environment, the unavailability of procurement as human resources within the Babinkum TNI environment and limited allocations The procurement of TNI Civil Servants from the Ministry of Defense of the Republic of Indonesia which was given to the TNI Babinkum resulted in a shortage of TNI and PNS personnel in carrying out their duties within the TNI Babinkum at all times. The purpose of this writing is to analyze the factors that influence the implementation of recruitment policies within the TNI Babinkum environment and provide solutions for implementing recruitment within the TNI Babinkum environment in carrying out its main duties. The research method uses qualitative methods with a post-positivist approach. The results of the research are that it is necessary to revise Article 78 letter a of TNI Perpang Number 33 of 2020 concerning the TNI Babinkum Organization, in particular it is necessary to coordinate the procurement of TNI Babinkum personnel with the TNI Commander Aspers, provide advice to the TNI Commander Aspers to plan the opening of special education for TNI Pa for legal professionals, recruit graduates military prosecutor position course, Ka Babinkum TNI coordinated with side and lower units to meet the needs of personnel within Babinkum TNI, reactivated civil service and administration courses whose graduates were recruited to become employees of Babinkum TNI.